Comparative study of different drying methods regard to the phenols and flavonoids content of dried Citrus aurantium L. leaves (Agro Productividad, 2021)
Objective: To determine the effects of different thermal drying technologies on the total phenol and flavonoid contents (TPC) and total flavonoids (TFC) in sour orange (Citrus aurantium L.) leaves.Design/methodology/approach: Solar drying was carried out in outdoor sunny conditions using two direct solar dryers; one with natural convection, the other with forced convection. The total phenol and flavonoid contents in gallic acid equivalents (GAE) and quercetin (Q), respectively, of ethanolic extracts of C. aurantium were assessed with spectrophotometric techniques.Results: The results demonstrated maximum phenol values for the direct natural convection solar dryer (161.4 mg EAG/g MS) and minimum values for shade drying (61.43 mg EAG/g MS). As for flavonoids, the highest values were obtained in the direct forced convection solar dryer (32.22 ± 1.6 mg EQ/g MS), while the lowest was registered in the open air sun (11.72 mg EQ/g MS).Conclusions: Direct solar dryers are technologies effective for maintaining the phenols and total flavonoids content in dried leaves of C. aurantium.